The Effect of Online Training on Employee Performance (a Study on Employees of the Efishery Start-Up) - Lestary, Fungky Nur (Advances In Social Humanities Research, 2025)
This study aims to determine the effect of online training on the performance of eFishery employees, particularly in the Operations Division, due to identified performance decline issues in this division. The proposed research hypothesis is that there is a positive and significant effect of online training on employee performance. The research method employed is quantitative associative causality, with two research variables: Online Training (X) as the independent variable and Employee Performance (Y) as the dependent variable. The research population comprises employees of eFishery’s Operations Division, with the sample consisting of all 85 employees in this division, as the sampling technique used is a census method. Data collection was conducted using a research questionnaire consisting of two measurement scales. Data analysis was carried out using simple linear regression analysis. The results of this study are as follows: (1) The level of online training is categorized as “moderate”; (2) The level of employee performance is categorized as “moderate”; and (3) There is a positive and significant effect of online training on eFishery employee performance.